EVALUATION OF THE PROCESS OF IMPLEMENTING TAHFIDZ AL-QUR'AN LEARNING PROGRAMS IN INTEGRATED ISLAMIC BASIC SCHOOLS OF DOD DELI SERDANG - Fakhruddin Azmi; Mesiono Mesiono; Abd Rahman (Sekolah Tinggi Agama Islam Al Hidayah, 2020)
This study aims to evaluate the implementation process of the tahfizh Alquran learning program at SDIT DOD Deli Serdang through one of the components of the CIPP evaluation model, namely, Process Evaluation. The research question is focused on; 1. How is the implementation of the Tahfzih Al-Quran learning program? 2. What are the supporting factors for the implementation of the Tahfzih Al-Quran Learning Program, and 3. What are the inhibiting factors for the implementation of the Tahfzih Al-Quran learning program at SDIT DOD Deli Serdang? This research was conducted at SDIT DOD Deli Serdang. This study used a qualitative research method with an evaluation approach as the blade of analysis. Sources of data were obtained from the head of the foundation, the principal, the deputy principal, the tahfizh teachers, the homeroom teacher and assistant, the students' parents, and the students, through three methods, namely observation, interviews, and documents. The results of this study are that the implementation of the program has not been as planned, the teacher has not mastered the learning material, the learning method varies with the adjustment of the student's ability level, has not used electronic-based learning media, the students have not been able to follow the memorization target, and not all students can repeat/learn ' ah memorization. Supporting factors for the Alquran tahfizh program at SDIT DOD Deli Serdang; The willingness of teachers to improve the quality of themselves in tahsin and tahfizh of the Koran, concern for parents, the establishment of a tahfizh Al-Quran learning program as part of the school's vision and mission, the enthusiasm of teachers in improving self-quality in reading and memorizing the Koran, communication between teachers and parents. Inhibiting factors for the Alquran tahfizh program at SDIT DOD Deli Serdang; Lack of budget, teacher quality, transfer students, teacher attendance, teacher ability, parents' ability Koran, school facilities, on average students have career parents. There is no awareness of students to repeat their memorization.